The expression of the lncRNAs USP30-AS1, ELFN1-AS1, GAS8-AS1, and SNHG11 in breast cancer samples from Iranian patients from 2014 to 2019: a cross-sectional study - Ghazal Orak; Zahra Orak Chahartangi; Zahra Nazeri; Fereshteh Ameli; Maryam Adelipour (BMC Research Notes)
Abstract Objective Breast cancer is a widely prevalent and life-threatening malignancy that affects women worldwide. The identification of novel molecular markers associated with tumor progression is highly important for enhancing early detection, tailoring treatment approaches, and monitoring therapeutic outcomes. In this study, we investigated the expression patterns of four long noncoding RNAs (lncRNAs): USP30 antisense RNA1 (USP30-AS1), ELFN1 antisense RNA1 (ELFN1-AS1), GAS8 antisense RNA1 (GAS8-AS1), and small nucleolar RNA host gene 11 (SNHG11). Results In breast cancer specimens, USP30-AS1 and GAS8-AS1 expression was decreased, whereas ELFN1-AS1 and SNHG11 expression was increased in breast cancer tissues compared with adjacent noncancer tissues. Decreased USP30-AS1 levels were associated with a smaller tumor size, lower tumor grade and stage, and the absence of lymphatic and vascular invasion. Lower GAS8-AS1 expression was associated with a lower tumor grade and positive estrogen and progestin receptor status. Elevated ELFN1-AS1 expression was associated with breast cancer that lacked P53 mutation. These changes suggest their promise as biomarkers for distinguishing between cancerous and noncancerous tissues.